2008
DOI: 10.1111/j.1468-8123.2008.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of continental crust influenced by internal and external forcing

Abstract: The permeability of continental crust is so highly variable that it is often considered to defy systematic characterization. However, despite this variability, some order has been gleaned from globally compiled data. What accounts for the apparent coherence of mean permeability in the continental crust (and permeability-depth relations) on a very large scale? Here we argue that large-scale crustal permeability adjusts to accommodate rates of internal and external forcing. In the deeper crust, internal forcing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 75 publications
2
64
0
Order By: Relevance
“…Interaction is promoted if the state of stress is close to failure so that the small changes in stress associated with either natural hydrologic processes or hydrologic responses to earthquakes can in turn influence seismicity. Rojstaczer et al (2008) proposed that this balance is reached by a feedback between hydrologic processes and seismicity. Rojstaczer et al (2008) suggested that one manifestation of this interaction is the value of the mean large-scale permeability of the crust -it should be of a size to accommodate internal forcing (fluid generation by metamorphic and magmatic processes) and external (groundwater recharge and discharge) forcing.…”
Section: Feedback Between Earthquakes and Hydrologymentioning
confidence: 99%
“…Interaction is promoted if the state of stress is close to failure so that the small changes in stress associated with either natural hydrologic processes or hydrologic responses to earthquakes can in turn influence seismicity. Rojstaczer et al (2008) proposed that this balance is reached by a feedback between hydrologic processes and seismicity. Rojstaczer et al (2008) suggested that one manifestation of this interaction is the value of the mean large-scale permeability of the crust -it should be of a size to accommodate internal forcing (fluid generation by metamorphic and magmatic processes) and external (groundwater recharge and discharge) forcing.…”
Section: Feedback Between Earthquakes and Hydrologymentioning
confidence: 99%
“…The excess pressure p is obtained from p ≡ P − gz, the difference between the absolute pressure at the transducer, P, and the hydrostatic level defined by the density of the fluid, , gravitational acceleration, g, and the depth of the transducer, z. In this equation, the permeability of the aquifer is assumed to be isotropic, an assumption that is violated when flow occurs predominantly within fracture networks [Rojstaczer et al, 2008;Ingebritsen and Manning, 2010].…”
Section: Relating Dynamic Pressures To Dynamic Strainsmentioning
confidence: 99%
“…Conversely, as suggested in another context [Chiodini et al, 2004], by overpressure transport, metamorphic fluid ascent may trigger itself permeability [Rojstaczer et al, 2008;Ingebritsen and Manning, 2010] and, thus, may induce the large microseismicity observed beneath the MCT zone [e.g., Pandey et al, 1999]. If the metamorphic CO 2 travels at such speeds, then some modifications in the crust, at the production point or along the way, can reach the surface within a few days.…”
Section: Resultsmentioning
confidence: 99%